2021
DOI: 10.1111/jgh.15426
|View full text |Cite
|
Sign up to set email alerts
|

Bedside risk‐scoring model for predicting 6‐week mortality in cirrhotic patients undergoing endoscopic band ligation for acute variceal bleeding

Abstract: Background and Aim: Acute variceal bleeding (AVB) is a fatal adverse event of cirrhosis, and endoscopic band ligation (EBL) is the standard treatment for AVB. We developed a novel bedside risk-scoring model to predict the 6-week mortality in cirrhotic patients undergoing EBL for AVB. Methods: Cox regression analysis was used to assess the relationship of clinical, biological, and endoscopic variables with the 6-week mortality risk after EBL in a derivation cohort (n = 1373). The primary outcome was the predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In terms of outcomes, 44 studies reported mortality, 810,18,2030,3237,39,4143,4749,5255,58,6366,6871,7375 27 rebleeding, 8,19,20,22,25,2931,34,35,38–40,43,45,46,50,51,5557,60,68,70,72,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of outcomes, 44 studies reported mortality, 810,18,2030,3237,39,4143,4749,5255,58,6366,6871,7375 27 rebleeding, 8,19,20,22,25,2931,34,35,38–40,43,45,46,50,51,5557,60,68,70,72,…”
Section: Resultsmentioning
confidence: 99%
“…The rate of HI/shock ranged between 1.2% and 68.3% of the eligible studies. The source of bleeding was UGIB in 54 of the included studies, [8][9][10][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]36,37,[39][40][41][42][43][44][45][47][48][49][50][52][53][54][55][58][59][60][63][64][65][66][67][68][69][70][71][72][73][74]…”
Section: Basic Characteristics Of Included Studiesmentioning
confidence: 99%
“…Through literature review of previous studies, we found three clinical predictive models that are similar to the UGIB‐LC score, including CAGIB score, MELDNa‐AGIB model, and the Bedside risk‐scoring model 33–35 . The variables of the CAGIB score include diabetes mellitus (DM), hepatocellular carcinoma (HCC), TBIL, ALB, ALT, and SCr.…”
Section: Discussionmentioning
confidence: 99%
“…Child-Pugh score, MELD score, and NLR as control methods to evaluate the UGIB-LC score in predicting the 6-week mortality of liver cirrhosis patients with acute UGIB, and revealed that the UGIB-LC score was superior to these scoring systems in predicting the 6-week mortality risk in such patients. Through literature review of previous studies, we found three clinical predictive models that are similar to the UGIB-LC score, including CAGIB score, MELDNa-AGIB model, and the Bedside risk-scoring model [33][34][35]. The variables of the CAGIB score include diabetes mellitus (DM), hepatocellular carcinoma (HCC), TBIL, ALB, ALT, and SCr.Zhao et al suggested that the CAGIB score was superior to Child-Pugh and MELD scores in predicting mortality in a F I G U R E 5 Calibration curve plot in the A, internal validation and B, external validation sets, showing good agreement between prediction and observation F I G U R E 6 The receiver operating characteristic (ROC) curve of upper gastrointestinal bleeding-liver cirrhosis (UGIB-LC) score, Child-Pugh score, model for end-stage liver disease (MELD) score, and neutrophil-to-lymphocyte ratio (NLR) in A, the training cohort and B, the validation cohort cohort of patients with HCC.…”
mentioning
confidence: 99%
“…We read with interest the paper "Bedside risk-scoring model for predicting 6-week mortality in cirrhotic patients undergoing endoscopic band ligation for acute variceal bleeding" published in the May issue of Journal of Gastroenterology and Hepatology. 1 The authors used Cox regression analysis to assess the relationship between clinical, biological, and endoscopic variables and 6-week mortality risk after EBL in a derivation cohort (n = 1373). The primary outcome was the predictive accuracy of the new model for the 6-week mortality in the validation cohort.…”
Section: The Complexities Of Predicting Outcome In Cirrhotic Patients With Acute Variceal Bleedingmentioning
confidence: 99%